PENGAWASAN PRODUK MAKANAN DAN MINUMAN ILEGAL OLEH DINAS PERINDUSTRIAN DAN PERDAGANGAN DI KOTA BAGAN SIAPI-API KABUPATEN ROKAN HLIR - Siis Kurnia; Ernawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Products Food And Beverage Illegal By The Department Of Industry AndTrade In Bagan Siapi-api Rokan Hilir, Supervision is the process in establishing performancemeasures and taking actions that can support the achievement of expected results in accordancewith set performance, as well as for achieving a goal that has been prepared and planned bycertain parties, especially government agencies with the aim of realizing the desire to beachieved, because the absence of an oversight, the objectives to be implemented will not be inaccordance with what has been in has designed. In relation to the above the Department ofIndustry and Trade in Bagan Siapi-api Rokan Hilir is one of the agencies authorized to conductsurveillance of food products and beverages illegally circulating in the city Bagan Siapi-apiRokan Hilir.The phenomenon that researchers have encountered, namely: still many outstanding foodand beverage products illegally from other countries in Bagan Siapi-api Rokan Hilir district.This study aims to identify and analyze how the monitoring of food products andbeverages illegal by the Department of Industrial and Trade In the city of Bagan Siapi-fire RokanHilir, and the factors that affect oversight. This research is descriptive qualitative where datacollection was done by using snowball.Keywords : Monitoring, Product Food And Drink Illegal, Department of Industry and Trade.